Research and applications in structural engineering, mechanics and computation : proceedings of the Fifth International Conference on Structural Engineering, Mechanics and Computation, Cape Town, South Africa, 2-4 September 2013 /: proceedings of the Fifth International Conference on Structural Engineering, Mechanics and Computation, Cape Town, South Africa, 2-4 September 2013. (2013) - Unknown
No abstract available